ANALISIS BUKU AJAR DEUTSCH IST EINFACH UNTUK SMA KELAS XI SEMESTER 1 - FADHILA FIRDAUS, ANISA (LATERNE, 2016)
In a process german learning is required textbook, because Prastowo in Lestari (2011:79) said that textbook is arranged for process of learning and contains learning materials which will be taught. A german textbook which is chosen should be appropriate with a good textbook criteria until can make students success. One of german textbook which exist is Deutsch ist einfach for SMA class XI semester 1. Based on the context of that problem, so the research questions are: How is the suitability of speaking skill exercises inside textbook Deutsch ist einfach for SMA class XI semester 1 with curriculum 2013? This research has purpose to know the suitability of the speaking skill exercises inside textbook Deutsch ist einfach for SMA class XI semester 1 with curriculum 2013. This research is qualitative’s desciptive research with documentation method. The datas are gotten from textbook Deutsch ist einfach for SMA class XI semester 1 which is written by Kasim. This speaking skill exercise research uses the theory of curriculum 2013. The results of this research indicate that: the speaking skill exercises in textbook Deutsch ist einfach for SMA class XI semester 1 are suitable with 5 scientific approaches in curriculum 2013, they are observing, asking, exploring, associating, and communicating. But there is still deficiency in speaking skill exercise 4.2.1 and 4.2.3 about imperative sentence which is not clear so it can make the students confused.   Key word: textbook, speaking skill